Biografika as a method for studying personalities: the search for sources - E. V. Medvedeva (Библиосфера)
The article shows the importance of studying the biographies of scientists and librarians and describes some strategies of information search on people who dedicated themselves to library profession and connected their life with the Scientific Library of Tomsk State University. An attempt is made to analyze main sources which help to study the history of the library, as well as life and activity of those people who made first steps in forming a university library community.